ABC (AUSTRALIAN BORN-CHINESE) :AN ANALYSIS OF RACE DISCRIMINATION ON "BIRDS OF PASSAGE", A NOVEL BY BRIAN CASTRO - I Wayan Yoga Handono, - (2011)
ABSTRACT This paper deals with a textual analysis of "Birds of Passage" novel. In analyzing the novel, the writer employs postcolonial criticsm which deals with the character portrayal and its relation with racist treatment toward the character. The paper also analyzes how the ABC (Australian Born-Chinese) is portrayed and the relation with the term of racism. In analyzing the portrayal above, the writer also identifes kinds of character portrayal and kinds of racism toward the ABC character which exist in the text. Based on the analysis, it is revealed that in the novel "Bird of Passage", the ABC character is portrayed in naming, beauty and/or ugly (physical appearance) and setting. Meanwhile, there is still bad streotype or negative prejudice of the people toward the ABC character, which rises the racist treatment toward the ABC. In the end, it is revealed that in the term of postcolonial criticism the ABC character draws as a hybrid identity person.